Institutional Dynamics and Skills Acquisition in School-Based Jewellery Education in Ghana - Mohammed Kwaku Baidoo; Akosua Tachie-Menson; Harry Barton Essel (Social Education Research, 2022)
School-based jewellery education in Ghana started at Kwame Nkrumah University of Science and Technology (KNUST), Kumasi, Ghana, in 1968. Jewellery graduates are expected to practice as jewellers in Ghana's jewellery industry. However, available information indicates that most jewellery graduates do not pursue careers in jewellery. The purpose of the study was to examine the institutional dynamics and skills acquisition of school-based jewellery education in Ghana. Against this background, the researchers sought to answer the research question: What are the processes and challenges involved in teaching and learning jewellery in school-based jewellery education in Ghana? The study adopted the mixed-methods research approach, with descriptive and evaluation as the main research methods used. A population of 90 respondents was drawn using total purposive and convenience sampling techniques, with observation, interviews, and questionnaires as data collection tools. Concern that most graduates of school-based jewellery education are not able to practice as jewellers is not a result of students not being trained well as jewellers; rather, the career paths of those jewellery graduates may be different.